Intestinal Delivery of Proinsulin and IL-10 via Lactococcus lactis Combined With Low-Dose Anti-CD3 Restores Tolerance Outside the Window of Acute Type 1 Diabetes Diagnosis - Cook, Dana P.; Cunha, João Paulo Monteiro Carvalho Mori; Martens, Pieter-Jan; Sassi, Gabriele; Mancarella, Francesca; Ventriglia, Giuliana; Sebastiani, Guido; Vanherwegen, An-Sofie; Atkinson, Mark A.; Van Huynegem, Karolien; Steidler, Lothar; Caluwaerts, Silvia; et al. (Frontiers in Immunology, 2020)
A combination treatment (CT) of proinsulin and IL-10 orally delivered via genetically modified Lactococcus lactis bacteria combined with low-dose anti-CD3 (aCD3) therapy successfully restores glucose homeostasis in newly diagnosed non-obese diabetic (NOD) mice. Tolerance is accompanied by the accumulation of Foxp3+ regulatory T cells (Tregs) in the pancreas. To test the potential of this therapy outside the window of acute diabetes diagnosis, we substituted autoimmune diabetic mice, with disease durations varying between 4 and 53 days, with syngeneic islets at the time of therapy initiation. Untreated islet recipients consistently showed disease recurrence after 8.2 ± 0.7 days, while 32% of aCD3-treated and 48% of CT-treated mice remained normoglycemic until 6 weeks after therapy initiation (P < 0.001 vs. untreated controls for both treatments, P < 0.05 CT vs. aCD3 therapy). However, mice that were diabetic for more than 2 weeks before treatment initiation were less efficient at maintaining normoglycemia than those treated within 2 weeks of diabetes diagnosis, particularly in the aCD3-treated group. The complete elimination of endogenous beta cell mass with alloxan at the time of diabetes diagnosis pointed towards the significance of continuous feeding of the islet antigen proinsulin at the time of aCD3 therapy for treatment success. The CT providing proinsulin protected 60% of mice, compared to only 17% when an irrelevant antigen (ovalbumin) was combined with aCD3 therapy, or to 17% with aCD3 therapy alone. Sustained tolerance was accompanied with a reduction of IGRP+CD8+ autoreactive T cells and an increase in Foxp3+CD4+ Tregs, with a specific accumulation of these Foxp3+ Tregs around the islet grafts after CT with proinsulin. The combination of proinsulin and IL-10 via oral Lactococcus lactis with low-dose aCD3 therapy can restore tolerance to beta cells in autoimmune diabetic mice, also when therapy is started outside the window of acute diabetes diagnosis.